Labile iron affects pharmacological ascorbate-induced toxicity in osteosarcoma cell lines. (2nd June 2020) - Zhou, Liangfu; Zhang, Lixiu; Wang, Shenghang; Zhao, Bin; Lv, Huanhuan; Shang, Peng
Abstract: Vitamin C and iron are both important nutrients for humans and involved in several physiological processes. The biological activities of vitamin C and iron are based on their abilities to accept or donate electrons. Although vitamin C is well known as an excellent electron donor in physiological conditions, it also has pro-oxidant properties, especially with catalytic metal iron. Cancer cells have a higher iron requirement than normal cells, which allows pharmacological ascorbate to kill cancer cells selectively. In this study, we demonstrated that the levels of H2 O2 in cells were significantly raised after treated with pharmacological ascorbate, and intracellular labile iron could increase pharmacological ascorbate-mediated oxidative stress by Fenton reaction. Catalytic metal iron plays opposite roles in and outside cells. Intracellular excess labile iron improved ascorbate-induced toxicity, while the excess labile iron in the medium abolished ascorbate-induced toxicity. Fe 3+ and Fe 2+ have the same effect on ascorbate-induced toxicity, but Fe 3+ chelator deferoxamine (DFO) has a profound inhibition effect than Fe 2+ chelator 2, 2′-bipyridyl (BIP) on ascorbate-induced toxicity. The influence of intracellular labile iron and ascorbate on the ferritin expression may cause selective sensitivity in osteosarcoma cell lines on pharmacological ascorbate. High iron requirement of many cancer cells facilitates pharmacological ascorbate on cancer treatment. In addition, increasing iron content in tumour tissue may be effective strategies to improve the effects of pharmacological ascorbate.